Occupational exposures and health-related quality of life in the Manaus Metropolitan Region, Amazonas State, Brazil: a cross-sectional study - Gustavo Magno Baldin Tiguman; Monica Caicedo-Roa; Marcus Tolentino Silva; Tais Freire Galvao (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2020)
Abstract: We aimed to investigate the association between occupational exposures and health-related quality of life among both informal and formal workers in the Brazilian Amazon. We conducted a cross-sectional study with working adults in the Manaus Metropolitan Region, Amazonas State, in 2015. Participants were selected through a three-step probabilistic sampling. The primary outcome was the health-related quality of life indicator, measured by the Brazilian validated version of the European Quality of Life 5-Dimensions 3-Levels (EQ-5D-3L) tool. Adjusted multivariate analysis was performed by Tobit regression and considered the complex sampling design. Results were converted to odds ratio (OR). Out of the 1,910 working individuals from the sample, 60.2% were formal workers. Informal workers were significantly more exposed to occupational risks than formal workers (p ≤ 0.05). Mean utility score for informal and formal workers was 0.886 (95%CI: 0.881; 0.890). Quality of life of informal workers was negatively impacted by exposure to noise (OR = 1.28; 95%CI: 1.13; 1.52), occupational stress (OR = 1.95; 95%CI: 1.65; 2.21), and industrial dust (OR = 1.46; 95%CI: 1.28; 1.72), while formal workers were negatively associated with exposure to chemical substances (OR = 1.58; 95%CI: 1.28; 1.87), noise (OR = 1.40; 95%CI: 1.23; 1.65), sun (OR = 1.65; 95%CI: 1.09; 1.40), occupational stress (OR = 1.65; 95%CI: 1.46; 1.87), biological material (OR = 2.61; 95%CI: 1.72; 3.97), and industrial dust (OR = 1.46; 95%CI: 1.28; 1.65). Exposure to occupational risks among workers from the Manaus Metropolitan Region was high, affecting both informal and formal workers. Brazilian policies need to be enforced to reduce the impacts on quality of life among workers in this region.